Pengaruh Brand Image, Persepsi Harga dan Kualitas Produk terhadap Loyalitas Pelanggan pada Pelanggan Kopi Soe di Kabupaten Jember - David Jaya Wardhana; Akhmad Suharto; Yohanes Gunawan Wibowo (BUDGETING : Journal of Business, Management and Accounting, 2023)
In the current era of globalization, competition in the business world is getting tougher. This becomes a demand for every company to be able to maximize the company's performance in order to be able to compete in the market. In the current era, many cafes have sprung up in Jember Regency. Soe Jember Coffee is one of the businesses in Jember Regency which is engaged in the culinary field. The competition that occurs requires all business sectors to provide the best service, for example strengthening brand image, determining the right price and good product quality. This research was conducted to determine the effect of brand image, perceived price and product quality on customer loyalty Coffee Soe Jember. This study uses multiple linear regression analysis with the population used is Coffee Soe Jember customers with a total sample of 100 people. This study shows that brand image, perceived price and product quality have a positive and significant effect on customer loyalty in Jember soe coffee. Keywords: Brand Image, Customer Loyalty, Price Perception, Product Quality